Pengaruh Motivasi Kerja dan Lingkungan Kerja Terhadap Kinerja Pegawai di Sekretariat DPRD Kota Bandar Lampung - Zulfa, Indana; Patmarina, Hepiana (Jurnal EMT KITA, 2024)
The purpose of this research is to determine the impact of work inspiration on the implementation of representation at the Bandar Lampung City DPRD secretariat, to determine the impact of the workplace on the implementation of representation at the Bandar Lampung City DPRD secretariat. Knowing the influence of work inspiration and the workplace on the implementation of representation at the Bandar Lampung City DPRD secretariat. This research uses a subjective exploration strategy with meeting techniques. The hypothetical premises used are inspirational, workplace, and representative execution hypotheses. Considering the consequences of directed exploration, it is reasonable that there is a positive and large impact between inspiration at the exhibition representing the Bandar Lampung City DPRD. Expanding inspiration within representatives can further develop worker performance, especially representatives of the Bandar Lampung City DPRD. There is a positive and critical influence between workplaces on the presentation of representatives of the Bandar Lampung DPRD. If offices increase, exhibitions will also increase or vice versa, if offices decrease, presentations will also decrease. There is a positive and critical influence between inspiration and the workplace on the presentation of representatives of the Bandar Lampung DPRD. Expanding inspiration and workplaces within representatives can further develop the performance of workers, especially workers in the Bandar Lampung City DPRD environment.